Challenges and strategies for sustainable heritage tourism development through local community empowerment - Fitriaty, Fitriaty; Amin, Shofia; Musnaini, Musnaini; Elliyana, Dessy; Widiatmoko, Agus; Saputra, Muhammad Haris; Larissa, Luna Laila (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
This research focuses on the critical challenges and strategies in developing sustainable tourism in the Jambi Province Heritage Site area by involving the active participation of local communities. Sustainable tourism is defined as an approach to tourism that aims to maintain sustainability in terms of economic, social, and environmental aspects. The research method approach includes the use of mixed methods, combining qualitative analysis using QDA Miner software and quantitative analysis with SmartPLS. The results showed that active local community empowerment and socio-cultural factors have a significant impact on sustainable tourism. The implications of this study highlight the need for a holistic approach that brings together the values of culture, nature and the tourism ecosystem to achieve sustainability goals. Sustainable tourism is not simply a replication of urban planning improvements, but must combine the values of nature, community cooperation, and cultural preservation with community welfare. This research provides a meaningful contribution in formulating sustainable tourism models and strategies that can be applied in Jambi Province, focusing on cultural and environmental preservation efforts and improving community welfare through local community empowerment to achieve sustainable tourism development.